THE EFFECT OF "AKU ANAK HEBAT" INTERVENTION ON STUDENTS’ SOCIAL SKILLS IN AL-MADINAH ISLAMIC KINDERGARTEN UNGARAN - Surya, Sartika; Erni Agustina, Setiowati (Journal of Psychology and Instruction, 2019)
This study aims to determine the effect of the intervention "Aku Anak Hebat" on students? social skills in Islamic Kindergarten Al-Madinah. This intervention is activities related to economic tokens. This study used an experimental method with one group pre-test post-test design. The subjects were 14 children obtained through screening by giving observation checklist 3 times in a row and teacher recommendations. Measurement of pre-test and post-test were done through observation checklist based on social skills criteria of children aged 4-6 years conducted by 4 raters. Data analysis used the Wilcoxon Sign test. The results showed that there was a significant influence after joining the "Aku Anak Hebat" program with a value of z = -2.032 with a value of p = 0.042 (two-tailed) <0.05. Research showed that the "Aku Anak Hebat" program is able to improve social skills in students in Islamic Kindergarten Al-Madinah.